Ethnography of Communication in the Suluk Tradition in Kubu Gadang, West Payakumbuh - Regina Regina; Nada Arina Romli; M. Fikri Akbar (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
This study aims to analyze the communication process within the Suluk tradition in Kubu Gadang, West Payakumbuh, using Dell Hymes’ Dell Hymes Ethnography of Communication approach. This research employed a qualitative method with an ethnographic approach through observation and in-depth interviews involving five informants and one triangulator, consisting of mursyid, khalifah, and salik. The findings reveal that communication in the Suluk tradition is systematically regulated to maintain participants’ spiritual concentration during the worship process. Communication occurs through verbal forms, such as dzikir, tawajuh, and spiritual instructions delivered by the mursyid, as well as non-verbal symbols, including the use of khalwat isolation tents, tasbih, and stones as counting tools. In addition, strict norms such as limiting speech, eye contact, and social interaction function as important non-verbal communication elements. These communication patterns collectively support the spiritual objectives of Suluk, particularly in strengthening self-discipline, inner focus, and closeness to Allah.